2016
DOI: 10.4187/respcare.04903
|View full text |Cite
|
Sign up to set email alerts
|

Silica Exposure and Effect on Peak Expiratory Flow: Slate Pencil Workers' Study

Abstract: Higher age, female sex, higher duration of exposure, and respiratory morbidity were found to be important correlates of PEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…PEFR in detecting obstructive changes in the respiratory tract using spirometer has a good correlation with the FEV1 (Tiwari, 2016). Earlier studies showed range values of 0.5 to 0.9, which were moderate to good correlation coefficients between percent predicted PEF and percent predicted FEV1 (Kelly and Gibson, 1988;Thiadens et al, 1999).…”
Section: Resultsmentioning
confidence: 90%
“…PEFR in detecting obstructive changes in the respiratory tract using spirometer has a good correlation with the FEV1 (Tiwari, 2016). Earlier studies showed range values of 0.5 to 0.9, which were moderate to good correlation coefficients between percent predicted PEF and percent predicted FEV1 (Kelly and Gibson, 1988;Thiadens et al, 1999).…”
Section: Resultsmentioning
confidence: 90%
“…Some cross-sectional studies have reported significant reductions in PEF. However, these studies provided no data on the levels of silica exposure [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent inflammation of the alveoli and further pulmonary fibrosis can result in irreversible ventilatory impairment in silicosis [ 32 34 ]. FEV1, FVC and PEF are important parameters to evaluate airway obstruction of workers with silica exposure [ 3 , 32 , 35 ].…”
Section: Discussionmentioning
confidence: 99%